Quercetin alleviates diastolic dysfunction and suppresses adverse pro-hypertrophic signaling in diabetic rats - Bartosova, Linda; Horvath, Csaba; Galis, Peter; Ferenczyova, Kristina; Kalocayova, Barbora; Szobi, Adrian; Duris-Adameova, Adriana; Bartekova, Monika; Rajtik, Tomas (Frontiers in Endocrinology, 2022)
Introduction Quercetin (Que) is a potent anti-inflammatory and antioxidant flavonoid with cardioprotective potential. However, very little is known about the signaling pathways and gene regulatory proteins Que may interfere with, especially in diabetic cardiomyopathy. Therefore, we aimed to study the potential cardioprotective effects of Que on the cardiac phenotype of type 2 diabetes mellitus (T2DM) accompanied by obesity. Methods For this experiment, we used Zucker Diabetic Fatty rats (fa/fa) and their age-matched lean controls (fa/+) that were treated with either vehicle or 20 mg/kg/day of Que for 6 weeks. Animals underwent echocardiographic (echo) examination before the first administration of Que and after 6 weeks. Results After the initial echo examination, the diabetic rats showed increased E/A ratio, a marker of left ventricular (LV) diastolic dysfunction, in comparison to the control group which was selectively reversed by Que. Following the echo analysis, Que reduced LV wall thickness and exhibited an opposite effect on LV luminal area. In support of these results, the total collagen content measured by hydroxyproline assay was decreased in the LVs of diabetic rats treated with Que. The follow-up immunoblot analysis of proteins conveying cardiac remodeling pathways revealed that Que was able to interfere with cardiac pro-hypertrophic signaling. In fact, Que reduced relative protein expression of pro-hypertrophic transcriptional factor MEF2 and its counter-regulator HDAC4 along with pSer246-HDAC4. Furthermore, Que showed potency to decrease GATA4 transcription factor, NFAT3 and calcineurin, as well as upstream extracellular signal-regulated kinase Erk5 which orchestrates several pro-hypertrophic pathways. Discussion In summary, we showed for the first time that Que ameliorated pro-hypertrophic signaling on the level of epigenetic regulation and targeted specific upstream pathways which provoked inhibition of pro-hypertrophic signals in ZDF rats. Moreover, Que mitigated T2DM and obesity-induced diastolic dysfunction, therefore, might represent an interesting target for future research on novel cardioprotective agents.